2021
DOI: 10.3390/children8080678
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of an Opioid-Free Anesthetic for Pediatric Circumcision in an Ambulatory Surgery Center

Abstract: Circumcision is one of the most common urologic procedures performed at pediatric ambulatory centers. Emerging data on the short- and long-term effects of perioperative opioid administration has highlighted the importance of an opioid-free anesthetic regimen. We sought to evaluate the effectiveness of an opioid-free anesthetic in pediatric circumcision and its correlation with ambulatory surgery center efficiency. Patients, 3 years of age and younger, who underwent circumcision or circumcision revision by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The reason may be that dexmedetomidine-assisted anesthesia reduces the stress-induced neuroendocrine response, stabilizes the child's hemodynamics, and reduces adverse effects and perioperative myocardial ischemia, thereby providing favorable conditions for the uneventful implementation of intraoperative and postoperative examinations and treatments. It has been shown [ 20 ] that the application of dexmedetomidine before induction of anesthesia provided stable hemodynamics, alleviated postoperative pain, and reduced the occurrence of agitation in children during the awakening period. Moreover, the results of the present study showed that the combined anesthesia resulted in a significantly lower incidence of complications and a high parent satisfaction versus total anesthesia ( P > 0.05), which was consistent with the results of previous research.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that dexmedetomidine-assisted anesthesia reduces the stress-induced neuroendocrine response, stabilizes the child's hemodynamics, and reduces adverse effects and perioperative myocardial ischemia, thereby providing favorable conditions for the uneventful implementation of intraoperative and postoperative examinations and treatments. It has been shown [ 20 ] that the application of dexmedetomidine before induction of anesthesia provided stable hemodynamics, alleviated postoperative pain, and reduced the occurrence of agitation in children during the awakening period. Moreover, the results of the present study showed that the combined anesthesia resulted in a significantly lower incidence of complications and a high parent satisfaction versus total anesthesia ( P > 0.05), which was consistent with the results of previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that handheld video games, DVD players, cartoons, music, virtual reality, and even video glasses significantly reduce levels of anxiety in children preparing to undergo surgery [6,[10][11][12]. In particular, when tablet-based distraction was compared to midazolam, improvements were seen in emergence delirium and length of stay, in addition to preoperative anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…Laura E. Gilberston and colleagues reported a study on the utilization of an opioid-free anesthetic for circumcision in an ambulatory surgery center. They reported a substantial decrease in in-room and postoperative recovery time with the utilization of this anesthetic approach [6]. Varicocele is a frequent pathology in adolescents, and laparoscopic varicocelectomy has gained growing popularity among pediatric surgeons.…”
mentioning
confidence: 99%